2004
DOI: 10.1002/hep.20074
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of mitochondrial DNA in liver under antiretroviral therapy with didanosine, stavudine, or zalcitabine

Abstract: A ntiretroviral therapy (ART) has significantly decreased the HIV-associated morbidity and mortality in industrialized countries. 1 ART usually consists of a combination of two nucleoside analogue reverse transcriptase inhibitors (NRTIs) with either protease inhibitors (PIs) or a nonnucleoside reverse transcriptase inhibitor (NNRTI), or of three NRTIs. 2 With prolonged exposure to antiretroviral drugs, clinicians became aware of long-term side effects of individual ART components. Many adverse effects of the N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
88
2
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(99 citation statements)
references
References 23 publications
(35 reference statements)
8
88
2
1
Order By: Relevance
“…Thus, Vittecoq et al 29 have reported a dissociation between mitochondrial evaluation in muscular biopsies and in peripheral leukocytes. Interestingly, Walker et al 30 reported a profound liver mtDNA depletion in patients treated with ddC and ddI, both highly toxic NRTI in vitro. mtDNA was also decreased in patients with elevated lactates.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, Vittecoq et al 29 have reported a dissociation between mitochondrial evaluation in muscular biopsies and in peripheral leukocytes. Interestingly, Walker et al 30 reported a profound liver mtDNA depletion in patients treated with ddC and ddI, both highly toxic NRTI in vitro. mtDNA was also decreased in patients with elevated lactates.…”
Section: Discussionmentioning
confidence: 99%
“…Protease inhibitors (PI) and nucleoside reverse transcriptase inhibitors (NRTI) have been related to insulin resistance 14 and lipodystrophy 15 ; NRTI may cause mitochondrial dysfunction with subsequent direct hepatotoxic effects. 16 Moreover, HIV infection itself may facilitate DM by way of tumor necrosis factor-a stimulation and mitochondria damage. 13 Also, other coexistent morbidities such as alcohol consumption or HCV infection may enhance steatogenesis.…”
mentioning
confidence: 99%
“…Lactic acidosis is a life-threatening complication of HAART with abrupt onset and uncharacteristic symptoms. ddI and d4T are strong inhibitors of polymerase-gamma which induces mtDNA depletion in adipose tissue and liver [1]. Respiratory chain dysfunction promotes liberation of reactive oxygen species at the respiratory chain, which can attack the respiratory chain itself or induce mitochondrial mutations, leading to mtDNA deletions.…”
Section: Discussionmentioning
confidence: 99%
“…MtDNA levels were profoundly depleted: liver 7%, kidney 20%, SM 28%, HM 72%. MtDNA of HM and SM were analysed for large scale deletions (8 HM/3 SM) [1]. Sequencing confirmed the DNA fragments to be mitochondrial.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation